Analysis of Cluster Interconnection Schemes in 802.15.4 Beacon Enabled Networks. (2008) - Mišić Mišić, Jelena Jelena; Udayshankar Udayshankar, Ranjith Ranjith
Abstract : In this paper, we consider the interconnection of IEEE 802.15.4 beacon enabled network clusters. We discuss two types of interconnections. One type can be achieved by using the PAN coordinator node as the bridging device and the other type is achieved by using ordinary network nodes as bridge nodes. We discuss design and performance issues of both kinds of interconnections.